EFFICACY OF PNEUMOCOCCAL INFECTIONS PROPHYLAXIS IN IMMUNOCOMPROMISED PATIENTS - E. V. Galkina-Lazareva ("Paediatrician" Publishers LLC, 2012)
Among immunocompromised patients morbidity and mortality rates from infections and infectious complications is significantly higher than in immunocompetent population. It is necessary to work out clear indications to vaccination of immunocompromised patients both with inborn and acquired immunodeficiency. Due to wider use of immunosuppressive therapy and introduction of new biological drugs with antycytokine actions, the number of secondary immunocompromised patients increases. The experience of specific prophylaxis of pneumococcal infection in different groups of patients with immunodeficiency is analyzed in this review.